2003
DOI: 10.1177/02698811030173013
|View full text |Cite
|
Sign up to set email alerts
|

Selective Processing of Smoking-Related Cues in Current Smokers, Ex-Smokers and Never-Smokers on the Modified Stroop Task

Abstract: The aim of this study was to investigate selective processing biases towards smoking-related stimuli in relation to acute abstinence and smoking history. Differences in the processing of smoking-related and control cues in current smokers, ex-smokers and never-smokers on the modified Stroop task were investigated, with smokers randomized to either abstain or smoke normally for a period of 24 h. The results indicated no significant effect of deprivation (abstinent versus non-abstinent smokers), or of smoking hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
123
6
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(146 citation statements)
references
References 22 publications
11
123
6
6
Order By: Relevance
“…For example, some cognitive features of nicotine dependence (e.g., cognitive processing bias for cigaretterelated cues) have been shown to decay completely in ex-smokers to the level of never-smokers. Munafò, Mogg, Roberts, Bradley, and Murphy (2003) used a modifi ed smoking Stroop task (i.e., smoking-related and neutral words in different colors) to test cueprocessing bias (i.e., greater latency to name the correct color) and found no difference between ex-smokers and never-smokers, whereas current smokers retained the bias. Assuming that this bias is a learned phenomenon, as Robinson and Berridge (1993) suggest, then this fi nding indicates that some smoking-related learning can weaken over time.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some cognitive features of nicotine dependence (e.g., cognitive processing bias for cigaretterelated cues) have been shown to decay completely in ex-smokers to the level of never-smokers. Munafò, Mogg, Roberts, Bradley, and Murphy (2003) used a modifi ed smoking Stroop task (i.e., smoking-related and neutral words in different colors) to test cueprocessing bias (i.e., greater latency to name the correct color) and found no difference between ex-smokers and never-smokers, whereas current smokers retained the bias. Assuming that this bias is a learned phenomenon, as Robinson and Berridge (1993) suggest, then this fi nding indicates that some smoking-related learning can weaken over time.…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere, research using this paradigm has produced mixed results; some studies have found smokers to show attentional bias towards smoking-related cues during abstinence (e.g. Gross et al 1993;Waters et al 2003) whilst others have reported such biases after recent smoking (Johnsen et al 1997); others still have reported no effect of abstinence versus recent smoking (Munafo et al 2003;Rusted et al 2000). In fact it is difficult to test the neurobiological model of addiction in relation to bias towards smoking-related words since both neurochemical and explicit cognitive processes, which affect attention towards such cues, are likely to be simultaneously involved, not necessarily working in the same direction.…”
Section: Discussionmentioning
confidence: 99%
“…Sur le plan clinique, ces phénomènes se traduisent par un risque accru de rechute, les stimuli liés à la fumée étant plus difficiles à ignorer (17,30,43,46). Ainsi, l'attention du sujet est retenue par un plus grand nombre de stimuli environnants liés au tabac (44).…”
Section: Dépendance Au Tabagismeunclassified